From 'unofficial militants' to de facto joint workplace control: the development of the shop steward system at the port of Liverpool, 1967–1972. (8th August 2017) - Taylor, Greig
Abstract: Prior to 1967, labour relations in the British dock industry had been characterised by casual employment, inter and intra-union conflict, frequent unofficial action and high strike occurrence. The Devlin Report and subsequent legislation decasualised employment in the industry and introduced official local shop steward systems. This article charts the evolution of local, post-Devlin, Registered Dock Worker (RDW) labour organisation at the port of Liverpool. A chronological approach to the major strikes and flash points will be accompanied by reflection on the historiography and theoretical perspectives relating to the form and nature of workplace mobilisation, 'shop stewardism' and labour organisation. The existing literature in this area focuses almost entirely on shop steward organisation in the manufacturing sector and emphasises the key role of leadership in the creation and maintenance of effective workplace organisation. However, the development of the shop steward movement at Liverpool docks was heavily contingent on historical traditions and conditions and was therefore not necessarily reliant on an elite stratum of politically conscious leader stewards to frame and direct grievance. The article concludes by comparing the existing literature with the evidence presented and questions whether those theoretical suppositions synonymous with shop floor and shop steward organisation in other industries are appropriate to the docks.